Crude and Nano Enhanced Antifungal Properties of Acalypha wilkesiana leaf extract against Trichophyton mentagrophytes (Lafia Journal of Scientific and Industrial Research, 2026)
Trichophyton mentagrophytes is a dermatophyte fungus responsible for infections of keratinized tissues such as the skin, hair, and nails. This disease can be caused by poor hygiene, a warm environment, and an individual's weakened immune system. In this study, we examined the antifungal properties of crude and nano-enhanced  Acalypha wilkesiana against T. mentagrophytes. Leaves of Acalypha wilkesiana were extracted with ethanol by maceration. Phytochemical analysis was conducted using conventional methods, and zinc oxide nanoparticles were prepared using a green synthesis technique. The Antifungal potential of A. wilkesiana was evaluated using the agar well diffusion test and microdilution method. The data were analyzed using two-way ANOVA, with a significance at P ≤ 0.001. The presence of alkaloids (5.82 ± 0.12 mg/g), flavonoids (8.35 ± 0.15 mg/g), and phenols (7.96 ± 0.21 mg/g) was noted during phytochemical screening. The gas chromatography-mass spectrometry (GC–MS) analysis confirmed ten compounds in the extract. Among the compounds, palmitic acid had the highest percentage peak (18.2%) with a molecular weight of 256 and a retention time of 5.43 minutes. The nano-enhanced formulation demonstrated greater inhibition zones than the crude formulation. Particularly, nano-formulated A. wilkesiana demonstrated significant improvement in antifungal properties against T. mentagrophytes (F = 1,261.50; P ≤ 0.001), with a zone of inhibition of 32.00 ± 1.00 mm compared to 23.00 ± 1.00 mm for the crude extract. Minimal Inhibitory Concentration (MIC) values showed a dose-response effect on the fungi.
Keywords: Antifungal resistance; Acalypha wilkesiana; Dermatophytes; ZnO nanoparticles